«Ya llegan, me dan sudores». El miedo al Moro en la comedia de magia española (siglos XVIII-XIX): reflexión sobre el imaginario colectivo - Lise Jankovic (Cahiers de Civilisation Espagnole Contemporaine)
Compared to the French Féerie, the Spanish Magical Theatre develops specific codes of representation. The figure of the Moor is analyzed in this paper, arguing that its presence on the Spanish Magical Stage is brought up by a marvelous evil imaginary. Our goal is thus to discuss this anachronistic fear as a product of the permanence of old conflicts and social types in the collective memory.